Bulk-fin field-effect transistor-based capacitorless dynamic random-access memory and its immunity to the work-function variation effect. (10th January 2023) - Lee, Sang Ho; Park, Jin; Kim, Geon Uk; Kang, Ga Eon; Heo, Jun Hyeok; Jeon, So Ra; Yoon, Young Jun; Seo, Jae Hwa; Jang, Jaewon; Bae, Jin-Hyuk; Lee, Sin-Hyung; Kang, In Man
Abstract: In this study, we developed a capacitorless dynamic random-access memory (DRAM) (1T-DRAM) device based on a junctionless (JL) bulk-fin field-effect transistor structure with excellent reliability and negligible variability against work-function variation (WFV). We investigated the variation in the transfer characteristics and memory performance of the memory cell owing to WFV. In particular, to investigate the WFV effect, we analyzed the transfer characteristics and memory performance of 200 samples using four metal-gate materials—TiN, MoN, TaN and WN. Consequently, we discovered that the WFV affected the transfer characteristics of the JL bulk-fin field-effect transistor. However, the proposed 1T-DRAM demonstrated that the sensing margin and retention time produced minimal effect owing to the adoption of a structure storing holes in the fin region. Consequently, the proposed 1T-DRAM exhibited strong WFV immunity and excellent reliability for memory applications.